Acceleration of Kirkendall effect processes in silicon nanospheres using magnetic fields. Issue 6 (26th January 2018) - Bian, Yuecheng; Ding, Wei; Hu, Lin; Ma, Zongwei; Cheng, Long; Zhang, Ranran; Zhu, Xuebin; Tang, Xianwu; Dai, Jianming; Bai, Jin; Sun, Yuping; Sheng, Zhigao
Abstract : We show that a magnetic field can act as an independent parameter to accelerate the Kirkendall effect in a liquid reaction system. Abstract : We show for the first time that a magnetic field can act as an independent parameter to accelerate the Kirkendall effect in a liquid reaction system. By taking silicon-based nanospheres as a model, it was demonstrated that a magnetic field could efficiently reduce the time of the Kirkendall effect processes at relatively low reaction temperatures. The hollow structure of the product obtained after 5 h under a magnetic field of 1 T is the same as that obtained after 24 h without a magnetic field.